Pengembangan Pariwisata dan Tingkat Pengangguran Terbuka: Bukti Empiris dari Sepuluh Destinasi Pariwisata Nasional Indonesia - Qorinul Huda; Muhammad Gozali Yahya; Setiawan Ariansyah; Ervan Nur Rahmat (Indo Publishing, 2026)
Tourism is a strategic sector expected to stimulate economic growth while reducing unemployment. However, its benefits have not been evenly distributed among local communities surrounding tourist destinations. This study examines the effect of tourism development on the Open Unemployment Rate (OUR) across ten National Tourism Destinations in Indonesia. The study employs panel data for the 2020–2023 period obtained from Statistics Indonesia (BPS) and the Directorate General of Fiscal Balance (DJPK). The analysis applies a Fixed Effects Model (FEM) estimated using the Feasible Generalized Least Squares–Seemingly Unrelated Regression (FGLS-SUR) approach. The results reveal that the number of guests and room occupancy rates in star-rated hotels have a significant negative effect on the Open Unemployment Rate, whereas the number of guests and room occupancy rates in non-star hotels, along with the proportion of government expenditure on tourism, have significant positive effects. These findings suggest that tourism development has not yet generated inclusive employment opportunities, particularly in the informal tourism sector and in the effectiveness of public spending. Therefore, tourism policies should prioritize greater local community participation, workforce capacity development, and more effective public expenditure to maximize employment creation.